Assessment of Parole and Probation Administration Program (PPAP) Implementation in Southern Negros Occidental: Perceived Effectiveness, Client Satisfaction, Challenges, and Opportunities - Cerbo, Joan; Verdeprado, Richelle; Madrigal, Dennis (Technium Social Sciences Journal, 2025)
This study assessed the effectiveness and client satisfaction of the Philippine Parole and Probation Administration's (PPA) programs in Southern Negros Occidental. Using a descriptive quantitative design, the study surveyed implementers and clients about core programs like the Therapeutic Community Treatment Modality, restorative justice, and volunteerism. Results indicate the program is highly effective and clients are highly satisfied, despite challenges such as limited resources, stigmatization, and a lack of family support. The findings suggest opportunities for program enhancement through tailored interventions, increased volunteer recruitment, and strengthened community linkages for job placement and counseling. The study's results offer a basis for an action plan to improve the PPA's services and support offender reintegration.